PEMAHAMAN PENGASUH PONDOK PESANTREN TERHADAP HADITS-HADITS MISOGINIS (Studi Kasus di Pondok Pesantren di Kabupaten Ponorogo) - Fahham, A. Muchaddam (EGALITA, 2007)
Gender bias in interpreting normative texts (Qur’an and Hadits) is one of significant factors to create gender inequality. The texts are interpreted by religious elites and the interpretation of the texts is accepted by society as an absolute truth which cannot be changed. This paper explores religious elite’s (Ulama) interpretation on Misogyny hadith in Ponorogo of which Heads of two pesantren (kyais) were interviewed their interpretation on the hadith. The data gathered were analyzed and were descriptively presented. The result shows that the Heads (kyais) from that Islamic boardinghouse ignored the methodology of interpretation particularly on the aspect of historical critics of the the chain of transmission (sanad) and the content (matn)of hadith. The heads of the two pesantren do not have special approaches in understanding hadith. Then, their understanding of the hadith may be discriminative toward women or vice versa.